Fortification of squid ink as a natural colorant on the acceptability of popping boba: Fortification of squid ink as a natural colorant on the acceptability of popping boba - Salsabila, Lulu; Liviawaty, Evi; Pratama, Rusky Intan; Rostini, Iis (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Ink is a fishery by-product that has the potential to be utilized as a natural colorant due to its melanin and melanoprotein pigment content, which is nutritionally valuable. This study aimed to determine the optimal concentration of squid ink as a natural colorant in popping boba based on consumer preference levels and chemical composition, and to evaluate its economic value. The research employed an experimental method using a completely randomized design (CRD) consisting of five squid ink concentrations (0%, 0.5%, 1%, 1.5%, and 2%) with three replicates. The parameters observed included hedonic tests (appearance, aroma, texture, and taste), chemical analysis (moisture, ash, protein, fat, and carbohydrates), and economic value. The results showed that the addition of 2% squid ink produced the most preferred popping boba, with appearance, aroma, texture, and taste scores of 7.9, 6.8, 7.9, and 7.1, respectively. The best popping boba formulation had a moisture content of 70.52%, ash content of 0.14%, protein content of 0.04%, fat content of 0.02%, and carbohydrate content of 29.34%. Therefore, fortifying popping boba with 2% squid ink provides an appealing color while also enhancing its nutritional value.